Selections from the records of the Government of India (Selections from the records of the Government of India, 1849-1937., 1984)
Includes Selections from the records of the Government of India (fiche no. 1-858, index no. 1-475), Selections from the records of the Bengal Government (fiche no. 858-997, index no. 476-555), Selections from the records of the Bombay Government (fiche no. 997-2098, index no. 556-1306)